KEPUTUSAN DIVERSIFIKASI TANAMAN UNTUK MENGEJAR PEMBANGUNAN PERTANIAN DI INDONESIA - Kartika Eka Pratiwi (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2021)
The narrative of agricultural development related to diversification and specialization in developing countries is still being debated. This study analyzes the determinants of diversification decisions according to the characteristics of food crop agriculture households in Indonesia and determines the characteristics of households that need intervention in agricultural diversification. By using logistic regression analysis, the results are obtained those farmers decide to diversify when conditions are limited in terms of income, land ownership not own property and poor crop conditions due to pest attacks. When conditions are more stable, for example, when they get older, the value of production has increased and they already have their own agricultural land, they tend to choose to plant one type of plant. Diversification is one solution to keep the supply chain for basic needs stable so that food security can be fulfilled.